Home quarantine - based rhythmic exercises: new fitness assessment and intervention in teaching physical education - Marino A. Garcia; Emerito R. Custodio (Physical Education of Students, 2021)
Background and Study Aim. The COVID – 19 pandemic has post threats on the physical and mental fitness of the people. Thus, the study determined the effectiveness of home quarantine - based rhythmic exercises to the fitness level of the university students in physical education.